Inland waterways, transport corridors and urban waterfronts - Antoine Beyer (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This paper analyses the opportunities and challenges of integrating inland waterways into transport corridors. Less than a fifth of the world's 623 000 kilometres of navigable inland waterways is currently used for freight transport. Although river transport has expanded in some countries, it is actually declining in others due to lagging investments or co-ordination. At the same time, urban development is encroaching on inland ports, reducing the space for logistics activities in many river ports, creating challenges for policy makers.
Keywords: 330